PEMBERIAN TUGAS MEMBUAT RINGKASAN SEBELUM DAN SETELAH PEMBELAJARAN UNTUK MENCAPAI KETUNTASAN BELAJAR MAHASISWA PADA MATA KULIAH KIMIA FISIKA I - Erna, Maria; Rery, R. Usman (Jurnal Pilar Sains, 2007)
Evaluation of students learning result at department of Chemistry educationFKIP Riau University on 1st Physical Chemistry subject is not reliable yet. It occursbecause students are not ready in lecture caused by less knowledge. It is necessary todevelop ad improve learning quality on this subject by giving task of doing summarybefore and after lesson. Subject of this research is student in 1st Physical Chemistry classon even semester 2006/2008. There are 32 student in this class. From summary sheetsbefore lesson, almost of all student make their summary in order basic theory. Whereasfrom summary sheets after lesson, student just write what was has been taught by lectureand not know much. Observation result as long as learning process shows that studenttrend are active. Development result shows 28 student achieve known degree ≥ 65% and4 students achieve know degree ≤ 65%. This result also shows that learning reliableclassically is of 87,5 %.Keywords: Reliable, Physical Chemistry, Summary